Exploring cerebrospinal fluid metabolites, cognitive function, and brain atrophy: Insights from Mendelian randomization - Liu Qian; Meng Ling-bing; Qi Tian-qi; Ma Ya-Qing; Liang Guo-wei (Open Medicine)
Disruption of cerebrospinal fluid (CSF) metabolites affects brain function and cognition, potentially altering the brain structure. To elucidate the causal relationships between CSF metabolites and the neurological outcomes, we conducted a two-sample Mendelian randomization analysis. Genome-wide association data from 689 individuals of European descent provided exposure levels for metabolites, analyzed alongside gene associations for cognitive performance (N  =  257,841), brain atrophy measures (cortical surface area and thickness; N  =  51,665), and hippocampal volume (N  =  33,536). Our analysis identified 30 metabolites exhibiting causal associations with brain atrophy and cognitive function: 20 linked to cognition and 10 to structural atrophy. Notably, butyrate correlated strongest with the cortical surface area, bilirubin with the cortical thickness, methionine sulfoxide with the hippocampal volume, threonate with cognitive performance, while oxidized Cys-gly, N6-succinyladenosine, and N-acetylglucosamine were linked to fluid intelligence, prospective memory, and reaction time, respectively. Pathway analyses revealed that butanoate and niacinamide/niacin ester metabolism are significantly associated with brain atrophy and cognitive performance. These findings position CSF metabolites as promising therapeutic targets for neurodegenerative diseases, providing a causal framework to prioritize interventions. Experimental studies building on this genetic evidence hold potential to accelerate the development of mechanism-driven therapies targeting metabolic pathways in neurodegeneration.